The Collaborative Role of Health Assistants, Healthcare Security, and Orthopedic Specialists in Enhancing Hospital Safety and Patient Care: A Systematic Review - Al-Otaibi, Salem Mishaan; Al-Harbi, Omar Ali Saleh; Almukhlifi, Rayan Qublan Abduldaim; Alotaibi, Abdullah Mukhlid Muslih; Alharbi, Mohammed Mana; Alotaibi, Naif Sunaytan Juaythin; AlKatheri, Mohammed Muneef; Al-Mutairi, Faisal Mohammed Zuwaid; Al-Mutairi, Abdulaziz Salman Dubyan; Alqahtani, Mohammad Shaban; Shafloot, Awad Saeed; Alotaibi, Khalid Mukhlid Muslih (Journal of Posthumanism, 2024)
Safety incidents in orthopedic wards, such as patient falls and aggression, are significant challenges that can impede recovery and compromise staff well-being. Globally, millions undergo orthopedic surgery annually, with a notable percentage experiencing preventable in-hospital complications. Standard hospital care models often feature siloed operations, where clinical, support, and security staff work independently, leading to fragmented communication and reactive safety management. An integrated collaborative care model, which fosters structured teamwork between orthopedic specialists, health assistants, and healthcare security, has been proposed as a promising alternative to proactively enhance safety and care quality. The primary aim of this systematic review is to systematically compare the effectiveness of an integrated collaborative care model versus standard siloed care on key hospital safety and patient care outcomes for patients in orthopedic units. A systematic search was conducted in PubMed, Scopus, CINAHL, and the Cochrane Library for studies published up to October 2025. We included randomized controlled trials (RCTs) and observational studies that evaluated collaborative models involving orthopedic specialists, health assistants, and security personnel. The PICO framework was used to define the population (orthopedic patients), intervention (integrated collaborative care), comparison (standard siloed care), and outcomes. Primary outcomes were patient fall rates and the incidence of security-related events. The review was conducted and reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. The search yielded 1,245 articles, of which 18 studies (6 RCTs and 12 observational studies) involving a total of 25,680 patients met the inclusion criteria. Studies implementing an integrated collaborative model demonstrated a statistically significant reduction in primary outcomes. Specifically, the collaborative model was associated with a pooled relative risk reduction in patient falls of 28% ($RR = 0.72$, 95% CI [0.65, 0.80]) and a 45% reduction in security incidents ($RR = 0.55$, 95% CI [0.48, 0.63]) compared to standard care. Secondary outcomes, including patient satisfaction and staff perception of safety, were also significantly higher in the intervention groups. The evidence strongly suggests that an integrated collaborative care model is more effective than standard siloed care in improving hospital safety and patient-reported outcomes in orthopedic settings. The implementation of structured, inter-professional teamwork protocols is a key strategy for creating a safer, more effective, and more humane care environment. Further research should focus on cost-effectiveness and the development of standardized implementation toolkits.